Formation of Uniform Water Microdroplets on Wrinkled Graphene for Ultrafast Humidity Sensing. Issue 15 (8th March 2018) - Zhen, Zhen; Li, Zechen; Zhao, Xuanliang; Zhong, Yujia; Zhang, Li; Chen, Qiao; Yang, Tingting; Zhu, Hongwei
Abstract: Portable humidity sensors with ultrafast responses fabricated in wearable devices have promising application prospects in disease diagnostics, health status monitoring, and personal healthcare data collecting. However, prolonged exposures to high‐humidity environments usually cause device degradation or failure due to excessive water adsorbed on the sensor surface. In the present work, a graphene film based humidity sensor with a hydrophobic surface and uniformly distributed ring‐like wrinkles is designed and fabricated that exhibits excellent performance in breath sensing. The wrinkled morphology of the graphene sensor is able to effectively prevent the aggregation of water microdroplets and thus maximize the evaporation rate. The as‐fabricated sensor responds to and recovers from humidity in 12.5 ms, the fastest response of humidity sensors reported so far, yet in a very stable manner. The sensor is fabricated into a mask and successfully applied to monitoring sudden changes in respiratory rate and depth, such as breathing disorder or arrest, as well as subtle changes in humidity level caused by talking, cough and skin evaporation. The sensor can potentially enable long‐term daily monitoring of breath and skin evaporation with its ultrafast response and high sensitivity, as well as excellent stability in high‐humidity environments. Abstract : A graphene film based humidity sensor is designed with a hydrophobic surface and uniformly distributed ring‐like wrinkles that exhibit excellent performance in breath sensing. The wrinkled morphology of graphene sensor can effectively prevent the aggregation of water microdroplets and thus maximize the evaporation rate.